Prevalence of oral precancer and cancer in south kerala population - Mathew, Anuna Laila; Daniel, Mathew Pothen; Cherian, Sunu Alice (Journal of Oral Diagnosis, 2017)
Introduction: Oral cancer is a major concern in developing countries. India accounts for one third of worlds oral cancer and has a high rate of oral precancer. Early detection of premalignant conditions can improve the prognosis of the disease. Objective: 1.To evaluate the prevalence of oral precancer and oral cancer among patients in south Kerala, India. 2. To evaluate the association of tobacco related oral precancer and oral cancer with abusive habits. Methods: A total number of 10999 patients, aged 20-80yrs, who visited the outpatient department of a dental college for the diagnosis of various complaints over a period of 8 months were interviewed for oral risk habits, duration and frequency of the habit and current usage of any medications. Patients were clinically examined by trained professionals. Result: The prevalence of oral precancer and cancer was seen in 1.08 % of the population. The prevalence of oral lichen planus was 0.72 % followed by leukoplakia 0.23 %, oral submucous fibrosis .072 %, oral cancer .036%, and erytroplakia .009%. Tobacco related oral lesions like leukoplakia, oral submucous fibrosis, oral cancer, erythroplakia were more prevalent among men as compared to women. The tobacco re- lated abusive habits like smoking and chewing tobacco were more prevalent among men. Conclusion: This study provides the prevalence of oral precancer and oral cancer among patients in South Kerala. It also reinforces the association between tobacco products and tobacco related oral precancerous lesions.